Estudio de la Seguridad en Redes de Sensores Corporales aplicadas al Ámbito Sanitario - Díez, Isabel de la Torre; Alonso, Carmen Marina Benito; Castillo, Gema; Alvarez, Aránzazu Berbey (KnE Engineering, 2018)
Nowadays, the technology has become necessary in daily aspects of everyday life, included healthcare and healthy lifestyle. Thus, in the last years has taken place an important development of Body Sensor Networks (BSN) to let a continuous monitoring. Security is becoming increasingly important in all areas related to Information Technology, and becomes even more important when patient’s health is involved. Confiability and privacy are necessary requirements for patients to feel secure with the sensors, but the reliability is necessary too, because if all measured data are lost or damage before reaching their destination, it cannot be made an adequate monitor or make the best diagnosis. The aim of this work is to provide a review of the security for BSN applied to the healthcare, in order to enable the development of applications to improve the patient’s diagnosis and treatment with chronic diseases. Keywords: BSN, healthcare,confiability, reliability, chronic diseases.